ANALYSIS OF OSMOSIS IN POTATOES: A STUDY OF CHANGES IN SIZE, TEXTURE, AND COLOR RESULTING FROM IMMERSION IN VARIOUS SOLUTIONS - Siti Nurhannisa; Meli Indriani Harahap; Salsabila A’Syifa; Nabila Sahila; Nadiyatun Najiyah (Journal Informatic, Education and Management (JIEM), 2026)
Osmosis is defined as the process by which water molecules move through a semipermeable membrane from a solution containing a lower concentration of solute to a solution containing a higher concentration. This study aims to observe the effect of various types of immersion solutions on changes in the physical properties of potato slices, including their size, texture, and color. The method used is an experiment by immersing four potato slices of the same size (length: 4 cm, width: 2 cm) in sugar solution, lime solution, plain water, and salt solution for 15 minutes. The results showed that potatoes immersed in the sugar solution became smaller in size (length: 3.5 cm, width: 1 cm), soft in texture, and pale in color. In the salt solution, potatoes also became smaller in width, softer in texture, and very pale in color. In contrast, potatoes immersed in plain water showed no significant changes, while those immersed in the lime solution only showed small changes in texture without affecting their size and color. This indicates that hypertonic sugar and salt solutions cause the release of water in potato cells. Plain water, which is a hypotonic solution, only causes slight changes. Meanwhile, the lime solution helped maintain the physical quality of the potatoes. The results of this study can be used as a science learning tool in elementary schools to help students understand the concept of osmosis in a simple and more realistic way.